Making up performance: the construction of “performance” in venture capital firms portfolios - Heinzelmann, Rafael (Proceedings of Pragmatic Constructivism, 2017)
Performance measurement is understood as a corner stone of organizations’ accounting and control function (Chenhall, 2003; Merchant & Van der Stede, 2012). In the wake of the relevance lost debate accounting systems have been criticized for being obsessed with historical financial accounting information making accounting data inadequate for decision making and insufficiently useful for creating a future alertness in organizations (Johnson & Kaplan, 1987). In the aftermath of this, more strategically-oriented accounting systems fostering on the non-financial dimension of performance, as most prominently presented by the balanced scorecard, gained increasingly attention by organizations and accounting scholars (Ax & Bjørnenak, 2005; Nørreklit, 2000, 2003). Yet, there is a substantial body of research studying the adoption of MAIs (Management Accounting Innovations) addressing questions of how MAIs such as the Balanced Scorecard travel and change in the course of diffusion and organizational implementation (e.g. Ax & Bjørnenak, 2005; Jones & Dugdale, 2002; Qu & Cooper, 2011). What the literature does not reveal in depth is how do integrated systems for performance measurement and control comprising financial and non-financial KPIs support organizations in handling uncertainty and complexity (Chenhall & Moers, 2015). In this paper, we aim for exploring performance measurement and control and thus contributing to existing literature by studying how venture capital firms mobilize ideas of performance measurement and control to handle uncertainty and complexity in their investment portfolio. More specifically, we investigate two firms of the venture capital industry that use financial and non-financial indicators to manage their portfolio and make decisions. Consequently, this paper addresses the following research questions: How do venture capital firms use performance measurement to manage their investment portfolios? And how is “performance” constructed in this context? Exploring how firms from a quite volatile industry use performance measurement is regarded to be interesting from various perspectives: First of all, we know little about the link between uncertainty and performance measurement. Second from a theoretical perspective of ActorReality Construction (ARC) there is little empirical evidence on how organizations construct facts or the factual dimension of accounting and management – facts in the context of our empirical setting, the venture capital industry, are measures used in the performance measurement system (PMS). Particularly, venture capital firms having a big stake in early phase seed investments, are uncertain in the sense that attaching a score or a number to a performance dimension of a portfolio company is maybe not that stable over time and ambiguous. However, doing the exercise of reviewing each portfolio company according to a dashboard-like PMS gives the KPIs, despite of their uncertain nature, a factual character. The PMS numbers allow managers to discuss and evaluate “performance” of the portfolio companies in management meetings as well as to make decisions, on for example, investing additional money, based on the performance facts of the portfolio company. Interestingly, the combination of “hard” and “soft” numbers – thus, financial and non-financial indicators, plays a pivotal role for VC companies in order to be capable to assess “the performance” of the portfolio companies. In other words, it enables venture capital firms to better take into account the particular organizational contexts of portfolio companies.